2021
DOI: 10.3389/fmicb.2021.683905
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and Microbiota Analysis Reveals the Conducive Effect of Pediococcus acidilactici BCC-1 and Xylan Oligosaccharides on Broiler Chickens

Abstract: Xylan oligosaccharides (XOS) can promote proliferation of Pediococcus acidilactic BCC-1, which benefits gut health and growth performance of broilers. The study aimed to investigate the effect of Pediococcus acidilactic BCC-1 (referred to BBC) and XOS on the gut metabolome and microbiota of broilers. The feed conversion ratio of BBC group, XOS group and combined XOS and BBC groups was lower than the control group (P < 0.05). Combined XOS and BBC supplementation (MIX group) elevated butyrate content of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Random forest analysis showed that both genus Faecalibacterium and Methanobrevibacter were important predictors of the CHE-induced lipid metabolism disorder. As aforementioned, Faecalibacterium belongs to Firmicutes, and it is a dominant member of gut microbiota, which might have a positive impact on fat synthesis and increased risk of excess lipid deposition in the chickens (82)(83)(84). We also observed that the hens under NEB condition caused by CHE, rather than initiated by lipolysis, increased the proteolysis to fill the energy deficit.…”
Section: Discussionsupporting
confidence: 63%
“…Random forest analysis showed that both genus Faecalibacterium and Methanobrevibacter were important predictors of the CHE-induced lipid metabolism disorder. As aforementioned, Faecalibacterium belongs to Firmicutes, and it is a dominant member of gut microbiota, which might have a positive impact on fat synthesis and increased risk of excess lipid deposition in the chickens (82)(83)(84). We also observed that the hens under NEB condition caused by CHE, rather than initiated by lipolysis, increased the proteolysis to fill the energy deficit.…”
Section: Discussionsupporting
confidence: 63%
“…Recent original investigations have also highlighted the increment of genus Methanobrevibacter in heat-stressed animals might lead to excessive fat accumulation through enhanced energy capture of the host ( 75 , 81 ). As for Faecalibacterium that belongs to the phylum Firmicutes , it was likely to be a biomarker for predicting the intestinal and systemic host health through its potential anti-inflammatory capability ( 82 , 83 ). However, Niu et al ( 84 ) reported that Faecalibacterium genus presents a positive relation with the abdominal fat and subcutaneous fat thickness in broiler chickens, and similar finding has been reported in the study of Gallardo-Becerra et al ( 85 ), who observed Faecalibacterium was significantly increased in obesity and positively correlated to BMI in humans ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several of these compounds are associated with nitrogen metabolism in the ceca or serve as cofactors for specific metabolic pathways. More recent, in vivo broiler studies by Wu et al (2021) delineated the impact of supplementing a combination of Pediococcus acidilactici BBC-1 and xylan oligosaccharides ( XOS ) in commercial broiler diets on the gut metabolome and microbiota. Both the xylan and Pediococcus supplements resulted in greater levels of O-acetylserine and the B vitamin pyridoxine while decreasing sorbitol.…”
Section: Other Microbial Metabolites Produced By Broiler Git Microbiotamentioning
confidence: 99%
“…Both the xylan and Pediococcus supplements resulted in greater levels of O-acetylserine and the B vitamin pyridoxine while decreasing sorbitol. Collectively, the metabolite data, along with the enrichment of specific metabolism pathways, led the authors to suggest that supplementation of both Pediococcus acidilactici BBC-1 and XOS accelerated cecal microbial fermentation ( Wu et al, 2021 ). Accelerated GIT microbial fermentation did align with the increase in butyric acid producing bacteria among the GIT microbiota of the birds fed Pediococcus acidilactici BBC-1 and XOS ( Wu et al, 2021 ).…”
Section: Other Microbial Metabolites Produced By Broiler Git Microbiotamentioning
confidence: 99%
See 1 more Smart Citation